3D gel-printing of hierarchically porous BCP scaffolds for bone tissue engineering. Issue 6 (June 2023) - Duan, Jing; Shao, Huiping; Liu, Hongyuan; Xu, Jing; Cong, Mengmeng; Zhao, Kedan; Lin, Tao
Abstract: In this study, a conventional technique of porous preparation was used to improve the constructive capability of direct ink writing on microstructures, and the hierarchically porous scaffolds were successfully prepared by 3D gel printing (3DGP). Micron-sized hydroxyapatite (HA) was coated with tricalcium phosphate (TCP) nanopowders synthesized by chemical co-precipitation to form biphasic calcium phosphate (BCP). The random structure of concave micropores was achieved by filling the BCP slurry with PMMA microspheres while successfully controlling the internal porosity of printed filaments. The results showed that the three-stage porous structure was successfully constructed, i.e., macroscopic pores of 1.50–2.00 mm, spherical micropores of 100–200 µm, and inter-powder interstices of 1.00–10.00 µm. Nano-TCP coated micron-HA powders improved the sintering activity of BCP particles. The compressive strength and porosity of the scaffolds sintered at 1400 °C were 2.78 MPa and 84.98%. The hierarchically porous BCP scaffolds had bright applications in bone tissue engineering.